2022
DOI: 10.1002/nbm.4827
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI with pulsed and free gradient waveforms: Effects of restricted diffusion and exchange

Abstract: Monitoring time dependence with diffusion MRI yields observables sensitive to compartment sizes (restricted diffusion) and membrane permeability (water exchange). However, restricted diffusion and exchange have opposite effects on the diffusion‐weighted signal, which can lead to errors in parameter estimates. In this work, we propose a signal representation that incorporates the effects of both restricted diffusion and exchange up to second order in b‐value and is compatible with gradient waveforms of arbitrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 128 publications
2
17
0
Order By: Relevance
“…References 10, 11 used oscillating gradient spin echo sequences rather than conventional pulsed gradient spin echo sequences to acquire diffusion data for the shortest two diffusion times (1.9 ms and 3.8 ms for Reference 1, 10, and 1.8 ms and 3.6 ms for Reference 11). As discussed by Chakwizira et al 23 this difference could affect the sensitivity to water exchange. While data points for these short diffusion times do appear in some of the figures in this paper, they are not part of our quantitative analysis.…”
Section: Methodsmentioning
confidence: 92%
“…References 10, 11 used oscillating gradient spin echo sequences rather than conventional pulsed gradient spin echo sequences to acquire diffusion data for the shortest two diffusion times (1.9 ms and 3.8 ms for Reference 1, 10, and 1.8 ms and 3.6 ms for Reference 11). As discussed by Chakwizira et al 23 this difference could affect the sensitivity to water exchange. While data points for these short diffusion times do appear in some of the figures in this paper, they are not part of our quantitative analysis.…”
Section: Methodsmentioning
confidence: 92%
“…Furthermore, we observed that MD increased, and FA decreased, with mean frequency of the power spectrum of q ( t ), demonstrating clear diffusion time effects in contrast to the in vivo data. This difference may appear due to the longer diffusion times used at the clinical scanner (a consequence of the relatively low gradient system performance in human MRI systems) and may be indicative of a higher permeability in myocardium compared with the plastic used in the phantom 64,65 . Here, we were limited by the size of the phantom; therefore, a preclinical scanner with high gradient performance was used.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may appear due to the longer diffusion times used at the clinical scanner (a consequence of the relatively low gradient system performance in human MRI systems) and may be indicative of a higher permeability in myocardium compared with the plastic used in the phantom. 64 , 65 Here, we were limited by the size of the phantom; therefore, a preclinical scanner with high gradient performance was used. Further development of more sophisticated phantoms, coupled with evaluation on clinical scanners, will add further insight.…”
Section: Discussionmentioning
confidence: 99%
“…( Olesen et al, 2022 ) As a consequence, we expect the values of to be lower than expected from histology and protocol dependent, as different gradient waveforms have different sensitivity to exchange, as well as there being potential bias due to microscopic GM kurtosis. ( Chakwizira et al, 2023 , Novello et al, 2022 ) The former point also indicates that a change in can be interpreted either as a change in its corresponding volume fraction or a change in the membrane permeability of the related cell population. The coarse spatial resolution was adopted to maintain acceptable signal-to-noise ratio (SNR) in the diffusion-weighted data, and despite the highly curved structure of the cerebellar GM, partial volume mixture with CSF and WM was minimised by the use of cerebellar segmentation, free-water elimination, and high b-value STE.…”
Section: Discussionmentioning
confidence: 99%